VD_FINDINFO HC / 2022 / 490 vom 16. Juni 2022 - VD Tribunal cantonal (2022)
TRANSACTION JUDICIAIRE, FRAIS JUDICIAIRES, DÉPENS | 105 CPC (CH), 109 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)